한국연구재단과 한국환경산업기술원 간 Eco-Bridge 구축방안에 관한 연구 - 우수 연구성과 연계 활용으로 부처간 벽 허물기 - 이종현; 권상숙; 정동일; 손지호; 차은종; 여무송; 이성종; 박귀순; Lee, Jong-Hyun; Kwon, Sang-Sook; Jung, Dong-Il; Son, Jiho; et al. (Daehan hwan'gyeong gonghag hoeji, 2013)
Korea is one of the top countries that has funded great amount to promote basic research and others in recent decade. While the quantity of R&D fund in Korea has rapidly increased, the effectiveness and quality of R&D outcomes became a controversial issue. National Research Foundation of Korea (NRF) and Korea Environmental Industry & Technology Institute (KEITI) agreed to collaborate for diffusing and utilizing R&D outcomes of each institute. NSF and KEITI signed the bilateral MOU in 2012, and Interministerial Collaborative R&D Support Framework (ICR&DSF) was developed. The ICR&DSF consist of launching an Eco-Bridge Program as an interministerial R&D program and composition of Environmental Convergence R&D Bridge Committee. The Eco-Bridge Program was applied to 'Environmental Convergence Technology Project' of KEITI as a pilot program in 2012. The unique feature of this interministerial R&D program is that the Eco-Bridge Program directly supports the basic research outcomes which are previously funded by NRF. As the collaboration between NRF and KEITI becomes stronger, it is expected to explore the more creative and the more transformative research. 국가연구개발 투자가 선진국 수준으로 증가함에 따라 투자 대비 성과 제고를 위해, 부처별 역할과 기능에 따라 상이한 소속부처(연구개발지원기관)간 협업의 필요성이 점차 부각되고 있다. 올해 출범한 신정부에서도 부처간 칸막이를 제거하고, 협업을 통한 국가연구개발사업 투자의 효율성 극대화를 정책목표로 제시하였다. 본 연구에서는 한국연구재단과 한국환경산업기술원 간 우수한 연구성과의 선순환적 활용을 위한 협력사업 추진과 Eco-Bridge 구축 방안을 제시하였다. 양 기관은 2012년 환경융합분야 관련 연구개발사업의 성과제고를 골자로 하는 양해각서(MOU)를 체결하였다. 이후 미래창조과학부와 환경부 간 기초연구성과의 실용화를 위해 한국연구재단 지원으로 기 수행된 기초연구과제를 대상으로 한국환경산업기술원에서 응용연구과제를 공모하는 방식의 협력체제를 국내 최초로 구축하고 환경부 공모 '2013년 환경융합신기술개발사업'으로 향후 3년 동안 약 20억원을 지원하게 된다. 또한 부처간 상설 협의기구인 '환경융합 Bridge 협의회' 설립 및 기초 R&D분야 연구자와 산업체 수요자를 상호 연계하는 Matching Program을 추진할 계획이다. 이와 같은 양 기관 협력체제는 기초 R&D가 시장 예측 및 수요를 기반으로 하는 R&BD의 형태로 발전하는 새로운 모델을 제시하고 나아가 부처별 연구지원 특성을 반영한 범부처 협력체계의 구축으로 국가연구개발사업의 효율성을 제고할 것으로 기대된다.